Rodzina w perspektywie studiów nad socjalizacją polityczną - Szczegóła, Lech (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
The aim of the paper is to present and discuss selected sociological approaches to problems of political and civic socialisation during rapid social changes. The paper is divided into two parts. Part one focuses on observations of the effects of five institutions, the agendas of political socialisation, such as family, school, church, mass media as well as peer groups. Research on their functions and dysfunctions has been a significant element of the picture of changes in the political culture of Poles since the beginning of the transition to the market system and democracy. Part two reviews debate over relationships between patterns of youth participation in politics and their origins, taking into consideration the socio-cultural context. The article analyses grounds for indicating that a reorientation in political attitudes and political behaviour of young people in contemporary Poland is probable. The theory of ‘silent revolution’ (Inglehart, 1977) has inspired this research.